2021
DOI: 10.14202/vetworld.2021.1760-1766
|View full text |Cite
|
Sign up to set email alerts
|

Etiopathological and hematobiochemical profiles in goats with gastrointestinal disorders

Abstract: Background and Aim: Gastrointestinal (GI) disorders in small ruminants limit production efficiency and productivity growth in the livestock sector, thereby directly preventing farmers from augmenting their income. This study aimed to provide detailed insight into the etiology, hematobiochemical parameters, and epidemiological risk factors of GI disorders in goats and to determine the pathology associated with the disorders. Materials and Methods: Over the period of 2018-2019, 500 goats in and around Bhubanesw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Some studies reported that there is a slight male predominance in MIS-C cases, 14 15 22 26 while others found slightly more female predisposition of MIS-C. 16 24 25 Our study did not find any gender predisposition which was similar to the other studies by Belhadjer et al, 27 Tiwari et al, 28 and Baradaran et al 29 Therefore, considering the data currently available, it cannot be opined that the probability of developing MIS-C is directly related with the sex of the patients. In our study, patients most frequently presented with persistent fever (100%), which is similar to findings in other studies about MIS-C. 15 23 30 31 32…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies reported that there is a slight male predominance in MIS-C cases, 14 15 22 26 while others found slightly more female predisposition of MIS-C. 16 24 25 Our study did not find any gender predisposition which was similar to the other studies by Belhadjer et al, 27 Tiwari et al, 28 and Baradaran et al 29 Therefore, considering the data currently available, it cannot be opined that the probability of developing MIS-C is directly related with the sex of the patients. In our study, patients most frequently presented with persistent fever (100%), which is similar to findings in other studies about MIS-C. 15 23 30 31 32…”
Section: Discussionmentioning
confidence: 99%
“…In different studies, the median age ranges of MIS-C cases were between the age of 6 and 10 years which is comparable to our study with a median age of 8 years. 14 15 16 22 23 24 25 26…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation